The Iraqi-Iranian War (1980-1988) And The International And Regional Situation - Mohammed Amin, Rafid Ahmed; Al-Deen, Salah (Opción, 2019)
The Iranian-Iraqi war has received a great deal of attention both internationally and regionally, because the geographical location of these two countries is very im- portant for the presence of oil wealth in the world, especially on the Gulf countries, in addition to the great oil resources found in the ground in the war mikkid. This war was a competitive struggle between two different states in every way. Each side of the conflict has goals and objectives in the region that are trying to achieve them, and they were completely convinced that when one of them gets what he wants, it is necessary not to achieve that for the other side. The Iraqi-Iranian dif- ferences did not remain before the start of the war in accordance with the concept of international conflict, which is often through conflict or transition to threat and pressure and bargaining and containment, but what happened, the differences be- tween the two countries has become clear and sharp through the media and verbal conflict . This conflict and conflict resulted in a military confrontation that lasted from 1980 to 1988, which caused a great deal of damage to both countries. The regional, Arab and international countries were far from observing that war and tried to intervene in order to influence the stirring up of that war. Intervention dip- lomatically or militarily and even the use of political means.